Serological Survey of Bovine Brucellosis in Cameroon - O. Shey-Njila; M. Daouda; E. Nya; P. A. Zoli; K. Walravens; J. Godfroid; S. Geerts (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2005)
A serological survey was carried out at the abattoir of Dschang (West Cameroon) from August 2002 to July 2003 in order to determine the prevalence of bovine brucellosis. Eight hundred and forty sera of cattle were examined for brucellosis by indirect ELISA (iELISA) and the rose bengal test (RBT). The seroprevalence of brucellosis was 9.64 and 4.88% by iELISA and RBT, respectively. Eighty-one samples that gave positive results in iELISA and 50 randomly selected samples that reacted negatively in iELISA and RBT were further tested by the complement fixation test (CFT) and the slow agglutination of Wright with EDTA (SAW-EDTA). All the RBT/iELISA negative samples were confirmed as negative by the other tests, suggesting that iELISA and RBT showed a high specificity in the tested population. Of the iELISA positive samples, 37.8% were classified as positive by SAW-EDTA, RBT, and CFT, 39.2% were classified as negative by SAW-EDTA, RBT, and CFT, and 23.0% were classified as positive by one or two of the three confirmatory tests. Given the lack of sensitivity of these confirmatory tests, particularly when chronicity of the infection and extensive husbandry systems (pastoralism) prevail, the best estimation of the actual prevalence of brucellosis was based on the iELISA results and was close to 10%.